ANALISIS TINGKAT KEBUGARAN JASMANI (VO2 MAX) PADA MEMBER SANGGAR SENAM JETIS GUNUNG PATI - Rosita .; Sugiharto . (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2021)
Physical fitness has been widely known to take an essential role in all sports specifically gymnastics. This sport needs a supreme physical state to achieve the optimal results, one of which is cardiopulmonary fitness. Cardiopulmonary fitness is commonly described as the maximum capacity to inhale, distribute, and use oxygen maximally (VO2 Max). The problem existing in this study is that the members of Jetis Aerobic Studio experience complaints due to the pandemic period such as loss of self-confidence since they are overweight. Almost all members as they come to do daily activities, such as experiencing shortness of breath, aches, sleeplessness, and potentially getting sick. The fear of Covid-19 virus has made those used to exercise worried of doing the same things in group. The research method applied here was descriptive quantitative. The collection technique used the observation survey method, while the data analysis technique utilized the statistical descriptive SPSS (minimum, maximum, mean). The results point out that based on all respondents, VO2 max has a minimum value of 26.80 ml/kg/minute, a maximum value of 47.10 ml/kg/minute, and a mean of 34.50 ml/kg/minute—with a Standard Deviation of ± 6.91. The conclusions are: based on analyses of physical fitness level (VO2 Max) on the members of the Jetis Aerobic Studio, the results are as follows: 20 samples are categorized by age, height, and weight. The sample average age is 28 years old and the average VO2 Max is 34.50 ml/kg/minute. The average VO2 Max in this study is categorized as good. Most of the gymnastics members have good endurance so that they are expected to maintain it by regularly participating in gymnastics seriously. If necessary, they can also add independent exercise in terms of physical exercise.